Safety of dry needling to the upper lumbar spine: a pilot cadaver study. (14th March 2020) - Mansfield, CJ; Harr, M; Briggs, M; Onate, J; Boucher, LC
ABSTRACT: Objective : When inserting a dry needle laterally into the upper lumbar spine (L1-L3) there is an increased risk of piercing the kidney; therefore, the objective of this study was to determine a zone of safety for practitioners to needle in the upper lumbar spine. Methods : Ten cadavers were screened for inclusion. L1 spinous process was identified and confirmed with ultrasound imaging. A digital caliper was used to measure laterally at 1.5 cm, 2.0 cm, and 2.5 cm. Dry needles were inserted maximally at each point and a binary decision, yes or no, was made to determine if bony contact was made. Needle depth and abdominal width measurements were also recorded. Safety of the dry needling procedure was interpreted as such if bony contact was made by the needle. If bony contact was made, then it was assumed that the needle cannot advance further into pleura or kidney. Results : Forty-four percent of needles did not make bony contact at 2.5 cm lateral of the L1 spinous process, whereas 22% did not make bony contact at 1.5 cm and 2.0 cm. There was a weak to moderate negative correlation between abdominal width measurements and needle depth at 1.5 cm (−0.48) and 2.0 cm (−0.45), and at 2.5 cm (−0.39). Conclusion : A safety zone of needling less than 2.5 cm is likely safe, but needs to be confirmed with future study. Dry needling 2.5 cm lateral appears more risky due to the higher frequency of not contacting a bony backdrop.